IVS – analysis of perioperative period - Surkont, Grzegorz; Wlaźlak, Edyta; Sobieszkoda, Dominika; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
The knowledge abort risks and possible complications during IVS procedure should minimize the frequency of complications, improve efficiency and hale positive influence on patients compliance. Data about complications are not often presented and probably their frequency is higher than we think. Materials and methods: Presented results are the part of bigger, prospective analysis which is aim is to compare Burch colposuspension and IVS. This part analyses perioperative period of IVS operation. We analyse first 70 procedures done by 2 operators according to suggestions made by prof. E. Petri (Germany). Results: Among complications there were: vaginal erosions (8,6%), haematoma in Retzius space, which needed to be evacuated (1,4%), haematoma which was not evacuated (2,9%), bladder injure without perforation (2,9%). We had no case of bladder perforation and no case of blood transfusion. Conclusions: Proper operative technique gives low pisk of complications during IVS procedure.